HUBUNGAN ANTARA ISAPAN BAYI DENGAN PRODUKSI ASI PADA IBU MENYUSUI DI RUMAH SAKIT ISLAM JEMURSARI SURABAYA - Tauriska, Tri Aprillia; Umamah, Farida (Jurnal Ilmiah Kesehatan, 2014)
The correlation between baby?s suck and breast milk production in breastfeeding mothers in RSI Jemursari Surabaya. The mothers feel reluctant to breastfeed their babies even though the exclusive breastfeeding has become a government?s propaganda. The pre-data taken from 15 breastfeeding mothers inform that 60% had a low breast milk production.  Purpose of this study was to find out the correlation between baby?s suck and breast milk production in breastfeeding mothers in RSI Jemursari Surabaya.The design of study was analytic-observational done by applying cross sectional approach. The population involved all breastfeeding mothers as imumnunization visiting the hospital with their babies, totally 18 people, in which 17 respondents were taken by using probability sampling technique. The instrument used for collecting the data was a checklist. The variables used in this study were baby?s suck and breast milk production. The data were analyzed by using Chi-Square test with the significance level ? = 0.05.The result of study showed that nearly all of the babies (94.1%) sucked correctly, whereas nearly all of the mothers (88.2%) had sufficient breast milk production. Moreover, the result of statistic test showed that p = 0.018 with the significance level ? = 0.05 so that p < ?. It also meant that H0 was rejected. The conclusion of study often the babies suck correctly, breast milk is produced. Hence, the breastfeeding mothers to still maintaining for breastfeed their baby with train them how to breastfeed correctly to increase breast milk production.